2021
DOI: 10.1038/s41598-021-94244-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic intraarterial catheterization with selective ICG fluorescence imaging in colorectal surgery

Abstract: The quality of mesorectal resection is crucial for resection in rectal cancer, which should be performed by laparoscopy for better outcome. The use of indocyanine green (ICG) fluorescence is now routinely used in some centers to evaluate bowel perfusion. Previous studies have demonstrated in animal models that selective intra-arterial ICG staining can be used to define and visualize resection margins in rectal cancer. In this animal study, we investigate if laparoscopic intra-arterial catheterization is feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In large animals whose aorta contains vasa vasorum, the originating arteries can be identified with assistance of imaging technology such as intravital microscopy or indocyanine green (ICG) fluorescence in live animals. [ 25 ] As early as in 1965, using X-ray microscopy, Clarke has identified that brachiocephalic and intercostal arteries feed ascending and descending aorta respectively, while the lumbar and mesenteric arteries feed the abdominal artery in post-natal humans. [ 26 ] It appears feasible to verify these vasa vasorum originating arteries in live animals such as porcine models using ICG fluorescence and perform selective intraarterial injections with TLR ligands to activate adventitial DC ( Figure 1 ).…”
Section: Induction Of Arteritis Via Vasa Vasorummentioning
confidence: 99%
“…In large animals whose aorta contains vasa vasorum, the originating arteries can be identified with assistance of imaging technology such as intravital microscopy or indocyanine green (ICG) fluorescence in live animals. [ 25 ] As early as in 1965, using X-ray microscopy, Clarke has identified that brachiocephalic and intercostal arteries feed ascending and descending aorta respectively, while the lumbar and mesenteric arteries feed the abdominal artery in post-natal humans. [ 26 ] It appears feasible to verify these vasa vasorum originating arteries in live animals such as porcine models using ICG fluorescence and perform selective intraarterial injections with TLR ligands to activate adventitial DC ( Figure 1 ).…”
Section: Induction Of Arteritis Via Vasa Vasorummentioning
confidence: 99%
“…In vivo fluorescence imaging technology provides a good application prospect for precision surgical navigation technology due to its instantaneous, high-resolution, and high-specificity detection advantages. Over the past few years, researchers have focused on near-infrared-I (NIR-I) and NIR-II fluorescence imaging, which has significantly improved imaging sensitivity, penetration depth, and spatial resolution. There are currently two clinically approved NIR fluorophores, methylene blue (MB, λ em = 700 nm) and indocyanine green (ICG, λ em = 800 nm), both of which are small molecules with the shortcomings of rapid clearance and easy leakage to the surrounding tissues. The development of fluorescent probes with high fluorescence efficiency, good water solubility, and good biocompatibility is of great significance to the development of fluorescence imaging technology.…”
Section: Introductionmentioning
confidence: 99%